Patient Satisfaction of Porcelain Veneer at the Odonto-Stomatology Hospital, Vietnam - Huong, Chu Thi Quynh; Hai, Trinh Dinh (European Journal of General Dentistry, 2023)
Objective The aim of this study was to study the clinical characteristics and patient satisfaction of the porcelain veneer aesthetic restoration at the Central Odonto-Stomatology Hospital, Vietnam.Materials and Methods This is a cross-sectional descriptive study of 94 teeth in 12 patients with indications for glass-ceramic restorations at the Department of Prosthodontics at the Central Odonto-Stomatology Hospital during the period from July 2021 to December 2022. Porcelain veneer aesthetic restorations in patients were evaluated using FDI World Dental Federation clinical criteria for the evaluation of veneer restorations for the esthetic parameters, functional parameters, biological parameters, and reliability. The evaluation was done immediately after installation and after 3 months. Evaluation of aesthetics, function, biology, and satisfaction was done using a scale (Scale 1–5). Data were analyzed using SPSS 18 software and descriptive statistics were calculated.Results It showed that the achieved results were good in terms of good to very good shape (100%) and good to very good color (98.8%). Three months after installation, the veneer restorations were stable in shape and color. The restorations were aesthetically and functionally satisfactory with no signs of broken or detachment.Conclusion Porcelain veneer restorations helped to improve the tooth shape and color. The patients were satisfied with the veneer restorations.
Keywords: porcelain veneers; veneer restoration; satisfaction